The Rb isotope composition of modern seawater and outputs to deep-sea sediments - Zhang, Xingchao; Tang, Limei; Du, Jianghui; Haley, Brian A.; McManus, James; Xia Hu; Huang, Fang (Earth and Planetary Science Letters, 2024)
{The rubidium (Rb) isotope system has the potential for tracing water–silicate interactions and providing information on the global Rb cycling. However, the Rb isotope compositions of modern seawater and its major inputs and outputs remain poorly understood. Here we measured Rb isotope compositions of seawaters, pelagic clay sediments and porewaters from the western and central equatorial Pacific Ocean. Our results show that the δ87Rb of modern seawater is homogeneous (0.13 ± 0.04‰; 2SD
Keywords: Modern seawater; Pelagic sediment; Porewater; Rubidium isotopes